2012
DOI: 10.1074/jbc.m111.334250
|View full text |Cite
|
Sign up to set email alerts
|

Highly Conserved Salt Bridge Stabilizes Rigid Signal Patch at Extracellular Loop Critical for Surface Expression of Acid-sensing Ion Channels

Abstract: Background: Plasma membrane expression is vital for the function of ASICs, which act as extracellular proton sensors. Results: Mutations in a conserved salt bridge and its adjacent region impaired cell surface ASIC expression. Conclusion: Surface ASIC expression involves an exposed rigid signal patch at the extracellular loop. Significance: This finding sheds lights on new strategies to prevent excessive neuronal excitability associated with ASIC activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 51 publications
(60 reference statements)
0
16
0
Order By: Relevance
“…Cell Surface Biotinylation and Western Blot Analysis-Surface biotinylation and Western blots were performed on cultured HEK293 cells according to our previous protocols (26,27). The HEK 293 cells were transfected with 8 g plasmids of HaFaNaC or its mutants (in pRc-CMV vector), 1.2 g plasmid of green fluorescent protein (as a transfection marker), and 15 l transfection reagent Hylimax.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell Surface Biotinylation and Western Blot Analysis-Surface biotinylation and Western blots were performed on cultured HEK293 cells according to our previous protocols (26,27). The HEK 293 cells were transfected with 8 g plasmids of HaFaNaC or its mutants (in pRc-CMV vector), 1.2 g plasmid of green fluorescent protein (as a transfection marker), and 15 l transfection reagent Hylimax.…”
Section: Methodsmentioning
confidence: 99%
“…First introduced into protein engineering in 1984 (32), double mutant cycle analysis was used to examine intramolecular and intermolecular interactions between proteins or a protein and its ligands (27,33,34). A double-mutant cycle involves a WT protein, two single mutants, and the corresponding double mutant protein.…”
Section: Double Mutant Cycle Analysis Indicates a Cooperative Mechanimentioning
confidence: 99%
“…Cell surface biotinylation and western blotting were performed as we previously described 24 . In brief, the HEK-293 cells transfected with rP2X4 or its mutants were washed in chilled PBS þ / þ , and then incubated with sulfo-NHS-LC-biotin.…”
Section: Methodsmentioning
confidence: 99%
“…This interaction is the most commonly observed interaction to contribute to the stability of the conformation of proteins (46 -48). Previous studies have demonstrated that a salt bridge is implicated in many protein functions, such as the ligand binding of the GABA A receptor (33), the stabilization of the activation state of Kir1.1 (37), the folding of the serotonin transporter (38), the surface expression of ASIC channels (34), and the protein thermostability of enzymes (36). Here, we suggest that the salt bridge formed between Arg-309 and Asp-85 played an essential role in the protein stability and channel gating of P2X4 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Salt bridges, commonly formed by a combination of noncovalent interactions (hydrogen bonding and electrostatic interactions) between acidic and alkaline amino acids, play important roles in maintaining the structures and functions of enzymes, receptors, and other proteins (30 -38). Previous studies have demonstrated important roles of salt bridges in channel functions, such as channel gating (31) and protein expression (34), in a wide variety of ion channels. Therefore, the reason why the polymorphism of one residue of this salt bridge induced loss-of-function in human P2X receptors should be reevaluated.…”
mentioning
confidence: 99%